Analisis Kinerja BAZ Nagari Sungai Pua Berdasarkan Indeks Zakat Nasional (IZN) dengan Pendekatan Dimensi Mikro - Husnul Fikri; Khadijah Ath Thahirah; Dedi Fernanda (Yayasan Almanar Pujud, 2024)
BAZ Nagari Sungai Pua until now has not measured its performance with the calculation method on the National Zakat Index. This measurement is important to find out at what stage the performance of the difference, both from the internal side of the institution and from the external side of the mustahiq who receive zakat benefits. This research method is descriptive research with a qualitative approach. The data analysis used by the author in this study is by calculating the National Zakat Index. The National Zakat Index (IZN) is a measuring instrument formed by the BAZNAS strategic studies center in 2016. IZN is a measuring instrument built with the aim of evaluating the development of different conditions. In the micro dimension, there are two indicators that become an assessment, the first is an institutional and zakat impact indicator. The performance of BAZNAS Sungai Pua based on the micro dimension index is good with an institutional dimension index value of 0.5. The value of the institutional aspect of the collection variable obtained a value of 0 which means very bad. Performance is seen from the aspect of zakat impact is 0.9. So the micro dimension assessment is the total of the indicators of institutional aspects and zakat impact, the value is 0.74 which means that the performance of BAZ Nagari Sungai Pua seen from the micro dimension is good.